Degree of administrative, physical and human requirements for the application of vocational education in the basic education stage Field study in Lattakia - Sbeira, Fouad; Ali, Saba (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to identify and management of human and material requirements for the application of professional education in basic education, , In order to achieve the objectives of the research were used descriptive and analytical approach by designing a questionnaire consisting of (38) is divided into three areas (administrative requirements, physical requirements, and human requirements), The research sample consisted of 187 male and female teachers in primary schools in the province of Latakia), Where the application of research in the first semester of the academic year (2017-2016). The research has come to several conclusions, it was the most important. -It came the degree of need for the administrative requirements (too high), while the degree of all came from the need of human and material requirements (high). - Lack of statistically significant differences in the degree of sample search on the questionnaire responses of individuals according to the loop variables (first, second) and the location of the school (city, countryside), Sex. - There are significant differences in the degree of sample search on the questionnaire responses of individuals in accordance with the Qualification Qualification top in favor of a variable.